2018
DOI: 10.1111/jcmm.13750
|View full text |Cite
|
Sign up to set email alerts
|

The oncogenic potentials and diagnostic significance of long non‐coding RNA LINC00310 in breast cancer

Abstract: Recent studies have revealed that long non‐coding RNAs (lncRNAs) are involved in different physiological processes and human diseases. However, to date, the function and overall clinical significance of the vast majority of lncRNAs in breast cancer remain largely unexplored. Here, we focused on LINC00310 by interrogating the breast invasive carcinoma data set of the Cancer Genome Atlas (TCGA). The results showed that LINC00310 was increased as breast cancer progressed, and the deregulation of LINC00310 was sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 51 publications
(53 reference statements)
0
11
0
Order By: Relevance
“…In recent years, more and more novel lncRNAs have been identified and the roles of lncRNAs in cancer development have been increasingly studied ( Yang et al, 2014 ; Bhan et al, 2017 ; Peng et al, 2017 ). In our previous study, we have shown the effectiveness of lncRNA signatures in diagnosis, prognostic prediction, and drug-resistance in four common cancers, namely breast cancer, colorectal cancer, bladder cancer, and lung cancer ( Li et al, 2017 , 2018a ; Xie et al, 2018 ; Zhan et al, 2018 ; Zhang et al, 2019 ). Here, we identified an 11-lncRNA model that was associated with tumor OS in ESCC patients, constructed a lncRNA-based molecular subtype of ESCC, and found that lncRNA AC007128.1 might mediate ESCC EMT through mitogen-activated protein kinases/extracellular signal-regulated kinase (MAPK/ERK) and MAPK/p38 signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, more and more novel lncRNAs have been identified and the roles of lncRNAs in cancer development have been increasingly studied ( Yang et al, 2014 ; Bhan et al, 2017 ; Peng et al, 2017 ). In our previous study, we have shown the effectiveness of lncRNA signatures in diagnosis, prognostic prediction, and drug-resistance in four common cancers, namely breast cancer, colorectal cancer, bladder cancer, and lung cancer ( Li et al, 2017 , 2018a ; Xie et al, 2018 ; Zhan et al, 2018 ; Zhang et al, 2019 ). Here, we identified an 11-lncRNA model that was associated with tumor OS in ESCC patients, constructed a lncRNA-based molecular subtype of ESCC, and found that lncRNA AC007128.1 might mediate ESCC EMT through mitogen-activated protein kinases/extracellular signal-regulated kinase (MAPK/ERK) and MAPK/p38 signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study has shown that the serumal and/or urinary exosome lncRNA profiles can be applied to the diagnosis and prognostic prediction of bladder cancer, colorectal cancer, breast cancer, and lung cancer ( Li et al, 2017 , 2018a ; Xie et al, 2018 ; Zhan et al, 2018 ; Zhang et al, 2019 ). In the present study, we used publicly available The Cancer Genome Atlas (TCGA) RNA-seq expression data and evaluated the potential effectiveness of lncRNA biomarkers for prognosis and subtyping of ESCC.…”
Section: Introductionmentioning
confidence: 99%
“…[30] LINC00310 was elucidated to promote cell proliferation by regulating c-Myc expression and serum LINC00310 expression exerted diagnostic significance in breast cancer. [31] LINC00462 promotes hepatocellular carcinoma progression through the PI3K/AKT signaling pathway. [32] In addition, LINC00462 also act as a target of miR-665 and activate the SMAD2/3 pathway by enhancing the expression levels of TGFBR1 and TGFBR2, and promote tumorigenesis in pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, lncRNAs seem to be measurable in body fluids, including the plasma, serum, and urine, empowering their potential as the non-invasive biomarkers for diagnostics of malignancies. For example, lncRNA XLOC_009167 can serve as a novel diagnostic biomarker for distinguishing lung cancer from benign lung disease and healthy controls (14); LINC00310, upregulated in breast tumors, is detected in the serum of breast cancer patients and serves as a promising diagnostic biomarker (15).…”
Section: Introductionmentioning
confidence: 99%